Missed Measles Immunisations Places Individuals and Communities at Risk: The Equity Argument for Including Measles in Under-Immunised Definitions - Stefanie Vaccher; Moses Laman; Margie Danchin; Fiona Angrisano; Christopher Morgan (Vaccines)
Background: Measles is consistently one of the leading causes of death from vaccine-preventable diseases in children, and cases and deaths have increased globally since 2019. While measles often serves as a ‘canary in the coalmine’ for health system weaknesses, global definitions of zero-dose and under-immunised children continue to centre on those who have missed diphtheria-tetanus-pertussis (DTP) containing vaccine. We propose that lack of receipt of measles vaccine is included in global definitions of ‘under-immunised’ children. Methods: We used publicly available WHO/UNICEF estimates of national immunization coverage (WUENIC) data to determine the number and proportion of children missing out on routine immunisations in each country globally in 2019 and 2022. We stratified countries by income status to further investigate inequalities in vaccine coverage between different countries. Results: In 2022, 50% more children missed out on their first dose measles-containing vaccine compared to DTP1, and 96% of these children resided in low-middle income countries (LMICs), highlighting the compounding inequities in measles immunisations globally. Furthermore, countries with the largest number of children missing out on DTP1 were not reflective of countries with the lowest measles immunisation coverage rates, suggesting targeted programs are needed to reach children who are missing out on measles vaccination. Recommendations: Given the high transmissibility and inequitable burden measles outbreaks pose to both at-risk individuals and communities, especially in LMICs, measles immunisation coverage should be included as a key metric when reporting and estimating the number of under-immunised children globally.